The Factors Associated With Performance Among Infection Prevention and Control Linked Nurse During Covid-19 Pandemic - Nita Fitria MH, RN, BSN; Henny Yulianita MN, RN, BSN; Firman Sugiharto RN, BSN; Dewanti Widya Astari MN, RN, BSN; Theresia Eriyani MHL, RN, BSN (SAGE Publishing, 2023)
Background Infection Prevention and Control Linked Nurses (IPCLN) are the spearhead of implementing the Infection Control Prevention Program. The performance of nurses in preventing and controlling infections during the Covid-19 pandemic greatly influenced the quality of services. Objective This study aimed to determine the factors that influence the performance of IPCLN during the Covid-19 pandemic. Methods Cross-sectional study was performed on 34 nurses at Cicendo Eye Hospital with a total sampling technique. The questionnaire in this study included knowledge, motivation, supervision, and the performance of nurses which had previously been tested with these characteristics with a result of Cronbach's alpha of 0.75. Data were analyzed using univariate, bivariate, and multivariate analyses. Results The mean score of IPCLN knowledge in this study was 14.82 ± 4.01, motivation 92.47 ± 15.85, supervision 34.74 ± 5.89, and performance 7.94 ± 2.71. There is a relationship between knowledge ( p  = .000), motivation ( p  = .000), and supervision ( p  = .000) on nurse performance. Motivation is the dominant factor influencing IPCLN performance compared to knowledge and supervision (Stand. Estimate = 0.5121; 95% CI = 0.1301-0.487; p  < .001). Conclusion Motivation is a dominant factor in IPCLN performance in this study. However, hospital management needs to maximize and make policies to improve IPCLN performance in terms of motivation. These policies can be through providing incentives for nurses, developing free continuing education programs, and issuing funds for nursing education scholarships.